ID: 132: LUPUS KERATINOCYTES ARE PRIMED BY AN AUTOCRINE TYPE I INTERFERON LOOP TO ROBUSTLY SECRETE IL-6. Issue 4 (22nd March 2016) - Stannard, JN; Reed, TJ; Kahlenberg, JM; Myers, EM; Lowe, L; Gudjonsson, JE
Abstract : Background: Cutaneous lupus erythematosus (CLE) is a disfiguring disease that can affect up to 70% of patients with systemic lupus. Treatment modalities are often ineffective and flares are frequent. Interleukin-6 (IL-6) is a pro-inflammatory cytokine which has gotten recent attention in SLE as IL-6 is increased in the serum of active patients and blockade of IL-6 is therapeutic in murine lupus models and phase I human trials. The source of IL-6 in CLE remains unclear. Methods: All studies were approved by the University of Michigan Internal Review Board (IRB# 72843 and 66116 to JMK). RNA was isolated from formalin fixed, paraffin-embedded biopsies of CLE rashes, which were obtained from the University of Michigan Pathology database. Real-time PCR was used to determine the expression level of the myxovirus (influenza virus) resistance 1 (MX-1) and interleukin-6 (IL6) genes. Biopsies were stained for IL-6 using immunohistochemistry. Skin biopsies were obtained from uninvolved skin of SLE patients with a history of cutaneous involvement or healthy controls followed by isolation and culture of keratinocytes. At confluence, cultures were treated with various concentrations of TLR ligands or UVB and IL-6 release was measured via ELISA. Blockade of type I IFN signaling was completed via monoclonal antibody to the type I IFN receptor. Results: Real-time PCR analysis of subacute cutaneous lupus erythematosus (sCLE) (n=21) and discoid (DLE) (n=22) rashes demonstrated a significant upregulation of both the IFN-regulated gene, MX1, and the pro-inflammatory cytokine IL-6 when compared with control samples (n=9). Immunohistochemical analysis of skin biopsies confirmed upregulation of IL-6 in the epidermis when compared to control. Keratinocytes from healthy skin of lupus patients produced significantly more IL-6 when stimulated by TLR2, 3 or 4 agonists or exposed to UVB radiation when compared to identical passage keratinocytes from healthy controls. Treatment of control keratinocytes with IFNα increased their IL-6 production and blockade of type I IFNs in the culture media of SKE keratinocytes downregulated the secretion of IL-6. Conclusions: IL-6 is increased at the RNA and protein level within cutaneous lupus biopsies when compared to healthy control skin. Keratinocytes are a major producer of IL-6 in the skin and lupus keratinocytes have enhanced production of IL-6 in response to TLR ligands and UV radiation. Exposure to type I IFN can increase IL-6 production in keratinocytes. SLE-derived keratinocytes downregulate IL-6 production in the presence of tonic blockade of the type I IFN receptor. These data suggest that the epidermis, which is an important barrier for environmental insults, is primed for IL-6 production by autocrine type I IFN production and that this may be one mechanism by which factors such as UV exposure may trigger rash development. Further investigations should focus on the pathogenic significance of IL-6 upregulation in the skin and whether targeting this pathway will have an impact on cutaneous disease activity.